Contribuições para a modelagem, analise, projeto e controle do conversor ressonante LLC driver de LED - Menke, Maikel Fernando (2021)
This work presents several contributions to the modeling, analysis, design, and control of the LLC resonant LED driver. Initially, the LLC resonant LED driver dynamic model accuracy is improved by taking into account under the modeling the LED non-linear electrical behavior instead of its equivalent load resistance. The extended describing function approach is employed. Simulation results show the feasibility of the proposed model, which predicts the real dynamic behavior of the LLC resonant LED driver when it operates around the main resonance. For the operation beyond the main resonance, the predicted behavior deviates from the real response. Afterward, the contribution to the LLC analysis is given by the proposed time-domain (TD) analysis, where the direct TD solution from the state-space representation is employed. The TD solution overcomes the classical first harmonic approximation (FHA) problem, which presents errors when the switching frequency ( fsw) is beyond the LLC series resonance. Compared to the TD procedure reported in the literature, the developed methodology presents a reduced number of assumptions, ensuring leading accuracy. Experimental results show an outstanding accuracy of the proposed method regardless of the operating condition (filter, load, input, etc.). Following, employing the proposed TD solution, a new design procedure for the LLC resonant LED driver is derived. This design procedure relies on the weighted-average-efficiency concept. Besides, different constraints are assessed to ensure zero voltage switching (ZVS), zero current switching (ZCS), enough power gain, and a practical fsw range over a wide operating window. Experimental results show the feasibility of the proposed design procedure, achieving high efficiency, ZVS, ZCS, and feasible fsw range over the whole operating range. The peak efficiency of 96.44% is achieved. In comparison to the classical design, the efficiency is improved up to 4.3%. Regarding the control system, the contribution is given by the proposal of a new hybrid dual-loop controller for the LLC resonant converter implementing the downstream DC/DC stage in an offline two-stage electrolytic-capacitor-free and flicker-free LED driver. The proposed controller is given by a PI subsystem and an adaptive periodic disturbance rejection subsystem, comprehending the proposed PI&APDR controller. Experimental results and simulation analysis show the outstanding performance of the proposed controller in comparison to conventional counterpart resonant-based controllers. Employing the PI&APDR controller the LED current DC reference is tracked over a wide operating range, even under parametric variations such as average bus voltage, resonant tank elements, and LED module. Besides, enhanced performance is achieved in reducing the output current ripple raised from the bus voltage ripple, where different bus voltage ripple frequencies are also considered. Furthermore, even employing non-linear adaptive controllers, the PI&APDR preserves the feature of having a simple design and implementation.